Comparative planning systems between Sarawak and Selangor : statutory process / Mohammad Yusup and Ahmad Fuzi Arshad - Yusup, Mohammad; Arshad, Ahmad Fuzi (2012)
This paper is written purposely to explain in detail the nature of the planning systems in Sarawak and Selangor by discussing the issues and differences in the main components of planning law. The state of Sarawak has been chosen as a subject of the paper due to the limitation of knowledge and documented research particularly on the planning system while Selangor has been chosen as a comparative subject because of the state's experiences in managing the development in urban areas. The differences in the planning systems between Sarawak and Selangor are because of the provisions in the Federal Constitution. Different planning systems brought together issues and problems especially in managing urban development, hence indirectly hindering the process of development in our country. The issues and problems are explained by the components of legal provisions from the overall perspective of legal framework, the planning administrative structure, the development plan mechanism and the development control system. This paper is actually part of a research conducted in fulfilling the requirement of masters degree in specialism in built environment.